Synergies between assisted reproduction technologies and functional genomics. Issue 1 (December 2016) - Loi, Pasqualino; Toschi, Paola; Zacchini, Federica; Ptak, Grazyna; Scapolo, Pier; Capra, Emanuele; Stella, Alessandra; Marsan, Paolo; Williams, John
Abstract This review, is a synopsis of advanced reproductive technologies in farm animals, including the discussion of their limiting factors as revealed by the study of offspring derived from embryos produced in vitro and through cloning. These studies show that the problems of epigenetic mis-programming, which were reported in the initial stages of assisted reproduction, still persist. The importance of whole-genome analyses, including the methylome and transcriptome, in improving embryo biotechnologies in farm animals, are discussed. Genome editing approaches for the improvement of economically-relevant traits in farm animals are also described. Efficient farm animal embryo biotechnologies, including cloning and the most recent technologies such as genome editing, will effectively complement the latest strategies to accelerate genetic improvement of farm animals.